KONSTRUKSI POSESIF BAHASA INDONESIA DALAM RUBRIK SURAT PEMBACA - Setiawan, Teguh (LITERA, 2016)
This study aims to describe characteristics of the relationship between the possessor and the possessed in Indonesian possessive constructions in letters to the editor. The research data were sentences with possessive constructions collected from letters to the editor in Kedaulatan Rakyat and Kompas daily newspapers in 2015. The data were collected by reading and noting and were analyzed by means of the distributional method to determine the possessive constructions and the correspondence method to determine the relationships between the possessor and the possessed. The findings are as follows. First, the possessive constructions in letters to the editor are in the form of noun phrases with two types of constructions, namely (1) Common Noun + Personal Pronoun, and (2) Common Noun + Proper Noun. Second, there are two types of relationships between the possessor and the possessed in the possessive constructions, namely the kinship and ownership relationships. The relationships can be categorized into two possessive relationships, namely the lexical/inherent possessive relationship (kinship relationship) and the extrinsic possessive relationship (ownership relationship).